VHDL Implementation of low power turbo coded OFDM physical layer for wireless communication - Shrimali, Yanita; Ballabh Sharma, Janki; S. Meena, R. (International Journal of Engineering and Technology, 2018)
Orthogonal Frequency Division Multiplexing (OFDM) is exceptionally favored system for rapid information transmission over remote channel. In this paper, VHDL implementation of low power turbo-coded OFDM (TCOFDM) Physical layer architecture is presented. In this architecture a low power memory-less pipelined FFT processor and Log-map turbo encoder/decoders are used to provide high throughput and lower complexity. Log-map turbo decoder provides high speed with good error correction capacity, while FFT/IFFT processor with single delay feedback (SDF) memory less architecture provide improved area and power efficiency. Proposed TCOFDM system is implemented using Xilinx ISE Design suite in the simulation results shows that the proposed scheme is having low power, high speed, high throughput and smaller area in comparison to other schemes.Â Â